6 yaş çocukları için mekansal algı ölçeği’nin geliştirilmesi ve mekansal algı eğitim programı’nın mekansal algı gelişimine etkisi - Tığcı, Figen (My University, 2003)
Mekansal Algı Ölçeği'nin Geliştirilmesi ve Mekansal Algı Eğitim nın Mekansal Algının Gelişimine Etkisinin incelendiği araştırmanın birinci bölümünde Mekansal Algı Ölçeği'nin geçerlilik ve güvenilirlik çalışması yapılmıştır. Son halinde 51 maddeden oluşan ölçekle ilgili olarak 5 okulun anasınıfına devam eden toplam 125 çocuk çalışma grubunu oluşturmuştur. Araştırmanın ikinci bölümünde Mekansal Algı Eğitim nın mekansal algının gelişimine etkisi incelenmiştir. Deneme modeline uygun olarak yapılan araştırmada 26 deney ve 26 kontrol olmak üzere 52 çocuk çalışma grubunu oluşturmuştur. Araştırmada veri toplamak amacıyla Mekansal Algı Ölçeği ve Raven Progressive Matrices Grup Zeka Testi kullanılmıştır. Araştırmadan elde edilen sonuçlara göre; Mekansal Algı Ölçeği geçerli ve güvenilir bir ölçektir. Mekansal Algı Ölçeği'nin iç tutarlılık katsayıları Cronbach Alpa için .8215; Spearman Brown için .7895; Guttman Split Half için ise .7889 olarak belirlenmiştir. İç tutarlılık katsayılarının 1'e yakın olması beklenen sonuç olup, ölçeğin iç tutarlılık düzeyi açısından güvenilir olduğu görülmektedir. 8 hafta olarak uygulanan Mekansal Algı Eğitim ocuklarına öntest ve sontest kontrol gruplu uygulanmış, elde edilen sonuçlara göre deney gruplarının öntest-sontest puanları arasında .05 düzeyinde anlamlı pozitif ilişki ve .01 düzeyinde sontest lehine anlamlı farklılık belirlenmiştir. Deney ve kontrol gruplarının sontest puanları arasında deney grubu lehine .01 düzeyinde anlamlı bir farklılık belirlenmiştir. Sonuç olarak bakıldığında, mekansal algının gelişiminde deney grubunda uygulanan Mekansal Algı Eğitim Programının, kontrol grubunda uygulanan geleneksel öğretim yönteminden daha fazla etkili olduğu anlaşılmaktadır. Araştırmanın sonucunda şu öneriler geliştirilmiştir: Mekansal Algı Ölçeği'nin norm çalışmaları yapılmalıdır. Mekansal Algı Eğitim buna benzer diğer eğitim programları ülkemiz gerçeklerine uygun olarak geliştirilerek uygulamaları yaygınlaştırılmalıdır. The validity and reliability study has been done in the first part of this research in which Development of Spatial Perception Scale and Effect of Spatial Perception Education Program on the Development of Spatial Perception is examined. A total of 125 children who go to kindergartens of 5 schools, related with the scale consisting of 51 items in its final phase, have constituted the study group. In the second part of the research, the effect of Spatial Perception Education Program on the development of spatial perception. In the research made in accordance with the experiment model, 52 children, of which 26 are experiment and 26 are control, have constituted the study group. Spatial Perception Scale and Raven Progressive Matrices Group Intelligence Test are used in the research to collect data. According to the results obtained from the research, Spatial Perception Scale is a valid and reliable scale. The internal coherence coefficients of Spatial Perception Scale is .8215 for Cronbach Alpha; .7895 for Spearman-Brown; .7889 for Guttman Split Half. The internal coherence coefficients' being close to 1 is an expected result, the scale is reliable with respect to the level of internal coherence. Spatial Perception Education Program has been applied for 8 weeks to the children of 6 years of age as preliminary test and final test control group, and according to the results, it has been determined that there is a meaningful positive relationship at a level of .05 between the preliminary test and final test points of experiment groups and a meaningful difference at a level of .01 in favor of the final test. It has been determined that there is a meaningful difference at a level of .01 between the final test points of experiment and control groups. Conclusively examined, ''Spatial Perception Education Program'' applied to the experiment group for the development of spatial perception is far more effective than the traditional education method applied to the control group. These recommendations have been developed as a result of the research: The norm studies of Spatial Perception Scale should be done. Spatial Perception Education Program and other similar education programs should be developed in accordance with the realities of our country and should be applied extensively.
Keywords: Eğitim; İlk öğretim; İlk öğretimin düzeyleri; Mekansal Algı; Okul Öncesi Eğitim”